Characterization of gas-solid reactions using in situ powder X-ray diffraction - Moller, Kasper; Hansen, B.; Dippel, A.; Jørgensen, J.; Jensen, T. (2014)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA , Weinheim. X-ray diffraction is a superior technique for structural characterization of crystalline matter. Here we review the use of in situ powder X-ray diffraction (PXD) mainly for real-time studies of solidgas reactions, data analysis and the extraction of valuable knowledge of structural, chemical and physical properties. Furthermore, the diffraction data may also provide knowledge on reaction mechanisms, kinetics and thermodynamic properties. Thus, in situ PXD simultaneously provides properties as a function of pressure, temperature and/ or time at different length scales, i.e. nanoscale structural data and bulk sample properties. Initially, a brief description of experimental and methodological details is provided, followed by a variety of examples of different designs of experiments and methods of data analysis. Additionally, it is discussed how a range of physical properties can be accessed by diffraction techniques, e.g. crystallite size. The aim of this review is to provide new inspiration for utilization of in situ PXD for characterization of a wide range of properties beyond the scope of crystal structure solution.